The Effect Of Self -Organized Learning Strategy On Learning To Perform Basketball Shooting Skills For Fourth -Grade Middle School Students (Journal of the College of Basic Education, 2025)
The research aimed to prepare educational units with the self -organized learning strategy for correction skills to perform correction skills (free throwing, shooting from jumping, peaceful correction) basketball for fourth -grade middle school students, and learn about the impact of self -organized learning strategy in learning to perform correction skills to perform correction skills (throwing Free, correction of jumping, peaceful correction) basketball for the fourth -grade middle school students, which assumed the researchers that there are statistically significant differences between the results of the tribal and dimensional tests of the experimental and controlled research groups in learning to perform correction skills (free throw, correction from jumping, peaceful correction)) Basketball, there are statistically significant differences between the results of the dimensional tests of the experimental and control groups in learning to perform correction skills (free throw, correction from jumping, peaceful correction) basketball, The experimental curriculum was adopted by designing the experimental and controlled groups, and the limits of the research community of the fourth -grade middle school students were represented in the distinguished secondary school for girls for the academic year (2023/2024), which number (95) students. (65) students (68.421 %) of this society, so that these two parties are the two research groups, the group control (35) students, and the experimental group (35) students, and after identifying research tests and preparing educational units in this strategy by one lesson per week for a period of (12 (A week for each skill to have (4) units, which were applied by experimenting with students of the experimental group, and after completion the results were addressed with the SPSS system (SPSS), Let the conclusions and recommendations be that the self -learning strategy has proven effective in practical lessons to learn to perform the correction skills of stability, correction of jumping, and a peaceful correction in the physical education lesson, and achieved a positive impact on motor learning of the correction skills of stability, correction of jumping, and a peaceful correction of students The fourth preparatory grade that they learn, and by superiority over the students who learn without them, and it is necessary to pay attention to enabling physical education teachers to apply the self -learning strategy in the self -education lesson for basketball and include this in preparation and training courses in the directorates of education.